Policy Reforms on Poultry Industry in Indonesia - Carmelo Ferlito (Center for Indonesian Policy Studies (CIPS), 2018)
The Indonesian poultry industry is a key sector for the national economy, supplying 65% of all animal protein and employing 10% of the national labour force. All over the country, though local production successfully copes with domestic demand, the potential for growth is high, consistent with expectations of rising GDP per capita. The market looks healthy and attractive, which has resulted in this gradual entry of new foreign groups. In past decades, the production process has evolved and modernized. The market is dominated by five main players-three foreign companies operating in feed production and two in day-old chick production. Even though expectations for the industry are strongly positive, prices for both broiler chicken and eggs are consistently higher in Indonesia than in Europe and America. From March- October 2018, Indonesian broiler chicken meat cost an average of about IDR 40,500/kg, while in the EU the price was around IDR 32,600 /kg (+24%). Over the same period, the average egg price in Indonesia was around IDR 28,000/kg, compared to just above IDR 21,000/kg (+33%) in the EU. The differences in price are partially due to differences in demand and supply- Indonesia is a Muslim country, so the demand for chicken meat may be stronger than in countries with higher pork consumption. However, Indonesia's higher prices are surprising given lower production costs. In Indonesia, farm salaries are lower than in Europe. In addition, the EU banned egg layer battery cages in 2012, forcing layer farmers to decrease bird density and therefore to implement more expensive methods of production, pushing up egg production costs. So production costs are higher in the EU, but consumer prices are lower. Price differences can also be explained in part by general market conditions in the EU and Indonesia. While the European market is a mature one, the constant growth in Indonesia, supported by growing demand, is an important element keeping prices high. While many economic factors are out of Indonesia's control, prices are also affected by Indonesian public policy. Therefore, we propose policy modifications that aim to support sound growth of the industry, which might be accompanied by lower prices. The first important act would be to resolve conflicts between existing regulations, in particular between Regulation of the Minister of Trade (MOT) 21/2018 and Regulation of the Minister of Agriculture (MOA) 57/2015 on the ministerial recommendation letter for maize import and maize import rights. Our second suggestion, related to MOA 26/2016, is to liberalize parent stock1 imports, enabling poultry producers to more freely implement sound entrepreneurial strategies rather than relying on incorrect government estimations. At the same time, we believe that it is necessary to open Indonesia to the international market for maize, rather than using trade protections to force local production. Current regulations have driven domestic maize prices incredibly high compared to the international price. Since maize is the main component of poultry feed, and feed is in turn the major cost in Indonesian poultry production, free access to international markets would heavily and positively affect production costs in the poultry industry, helping prices to cool down. Finally, the government could play an important role in improving infrastructure, which, at the moment, burdens the industry-particularly in the case of transporting raw materials for feed from the ports to the mills. An improvement in road infrastructure would also allow the transport of heavy machinery, further boosting modernization of the poultry industry.
Keywords: O13; P16; 330; Poultry market; Indonesia; Political Economy; Free Trade